Silica aerogel infused hierarchical glass fiber polymer composites - Anthony,DB; Nguyen,SN; Qian,H; Xu,S; Shaw,CMD; Greenhalgh,ES; Bismarck,A; Shaffer,MSP (Composites Communications, 2023)
Hierarchical systems can address the matrix-dominated failures of structural fiber polymer composites. Here, a new synergistic hierarchical structure combines conventional structural glass fibers with a bi-continuous silica-based aerogel matrix; both pure-silica and organically-modified silicate aerogels are demonstrated. When infused with an epoxy matrix, this type of hierarchical architecture showed a marked improvement in mechanical properties: without any loss in modulus, both the compressive strength and the interlaminar shear strength increased by up to 27%, relative to the equivalent glass-fiber reinforced epoxy composite baseline. The bi-continuous network modification strategy uses industrially-relevant infusion techniques, at or near room temperature, and retains a similar final composite density (within 2%). The strategy presented here provides a versatile and readily applicable means to improve state-of-the art continuous fiber reinforced composite systems in compression and offers an opportunity to develop a new generation of composite materials.